The advertising French media text as a method of forming the foreign language students’ intercultural competence - Д. А. Руснак (Іноземні мови, 2018)
Introduction. Teaching intercultural communi! cation is the main objective of university student’s study. The forming of intercultural competence is very important for the foreign language students. There are two ways to realize the intercultural communication: by the direct contact with the native speaker and through authentic texts. The forming of intercultural competence is possible by using the authentic media texts in the teaching process at university. Purpose. The purpose of the article is to consider the particularities of advertising French media text as a method of forming the intercultural competence. Methods. Analysis of socio-psychological and methodo- logical scientific sources on advertising texts in French and of different types of stereotypes, as a component of culture, has been used. Results. An advertising text as an example of the modern aid of foreign language students’ intercultural competence forming is presented in the article. The content of intercultural competence is described. A stereotype as a form of social representations is characterized. The role and place of stereotypes in French advertising text are described. The stages of working with the advertising videotext are described. An example of methodic project of the video advertising text is proposed. The conclusion has been made: the advertising text as a rich source of language and cultural information let form students’ intercultural competence along with others foreign communicative competences. The prospective of the further research is selecting French and Ukrainian advertising texts that can be used for teaching students intercultural communication.